Application of allograft and absorbable screws in the reconstruction of a massive bone defect following resection of giant osteochondroma: A retrospective study - Ma, Zhihao; Yang, Qiang; Liu, Xinyu; Li, Zhenfeng (Frontiers in Surgery, 2022)
Background: This study aims to introduce a reconstruction method that applicating allograft and absorbable screws to repair large bone defects caused by the resection of giant osteochondroma. Methods: A retrospective study of a series of patients who underwent the resection of giant osteochondroma reconstructed by allograft and absorbable screws was conducted from February 2020 to September 2021. Their demographic data, location site, osteotomy length, and pertinent operative details were recorded. Reconstruction modality allograft was elaborated. In the follow-up, radiographic images were utilized to determine bone union, and the Musculoskeletal Tumor Society (MSTS) score was used to evaluate the postoperative limb function. Results: A total of 7 patients were included, including 3 males and 4 females with an average age of 16.6±6.5 years. Among them, 3 cases of tumors occurred in the humerus and 4 cases in the femur. The average follow-up time was 11.3±3.0 months. The average area of bone graft was 25.9±8.3 cm2. No complications such as infection, nonunion, and allograft bone fracture were found during the follow-up period. At six months after operation, the average MSTS score was 26.4±1.6 with acceptable postoperative function. Conclusions: The cooperative application of absorbable screw fixation and allograft including mixed cortical bone and cancellous bone, which yielded satisfactory functional outcomes and acceptable postoperative complications, is an effective reconstruction method for a massive bone defect after the resection of giant osteochondroma.